2002
DOI: 10.1063/1.1486257
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of absorption in photorefractive iron-doped lithium niobate crystals

Abstract: We present experimental data showing a significant dependence of light absorption on temperature in photorefractive LiNbO 3 :Fe crystals. The results are successfully explained by assuming that the widths of the Fe 2ϩ absorption bands in the visible and in the infrared spectral region depend on temperature. The findings are of relevance for thermal fixing of holograms. Furthermore, a temperature-induced increase of the infrared absorption is promising for improved infrared recording.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…The knowledge of the temperature evolution of the absorption bands in the visible is crucial due to the fact that the nonvolatile recording becomes possible at elevated temperatures. The recent work by Panotopoulos et al [5] has been the first address to the issue of temperature dependence of absorption in LiNbO 3 :Fe crystal. They reported that the absorption Fe 2+ band broadens while the peak absorption energy does not shift as the temperature is increased up to 150 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of the temperature evolution of the absorption bands in the visible is crucial due to the fact that the nonvolatile recording becomes possible at elevated temperatures. The recent work by Panotopoulos et al [5] has been the first address to the issue of temperature dependence of absorption in LiNbO 3 :Fe crystal. They reported that the absorption Fe 2+ band broadens while the peak absorption energy does not shift as the temperature is increased up to 150 °C.…”
Section: Introductionmentioning
confidence: 99%
“…That means that the changes that take place directly during the cooling process escape observation. We know of only two publications [23,24], where in situ investigations of optical absorption were carried out for Fe-doped LN crystals in the spectral region of absorption of the Fe ions, however in a narrow temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…There are two ways of transverse and longitudinal uses for LN.In the transverse use,the total phase delay is not only proportional to the applied voltage,but also related to l/d [5].Therefore, the half wave voltage can be greatly reduced with the increase of l or decreasing d .In this paper,we take transverse voltage mode.…”
Section: Ln Voltage Estimationmentioning
confidence: 99%